In response to crisis: the use of songs to respond to multiple crises in Yusuf Islam (Cat Stevens)' post-conversion lyrical compositions - Azwar Tahir (Center for Humanities and Innovation Studies, 2022)
Yusuf Islam, also known as Cat Stevens, is a well-known singer and songwriter. He had decided to avoid the music industry for many years. He focused more on humanitarian activism as well as building educational institutions in London. In 2006, through the release of the album entitled